Urine gastrin‐releasing peptide in the first week correlates with bronchopulmonary dysplasia and post‐prematurity respiratory disease. Issue 4 (29th January 2020) - Voynow, Judith A.; Fisher, Kimberley; Sunday, Mary E.; Cotten, Charles M.; Hamvas, Aaron; Hendricks‐Muñoz, Karen D.; Poindexter, Brenda B.; Pryhuber, Gloria S.; Ren, Clement L.; Ryan, Rita M.; Sharp, Jack K.; Young, Sarah P.; et al.
Abstract: Rationale: Bronchopulmonary dysplasia (BPD) is associated with post‐prematurity respiratory disease (PRD) in survivors of extreme preterm birth. Identifying early biomarkers that correlate with later development of BPD and PRD may provide insights for intervention. In a preterm baboon model, elevated gastrin‐releasing peptide (GRP) is associated with BPD, and GRP inhibition mitigates BPD occurrence. Objective: We performed a prospective cohort study to investigate whether urine GRP levels obtained in the first postnatal week were associated with BPD, PRD, and other urinary biomarkers of oxidative stress. Methods: Extremely low gestational age infants (23‐28 completed weeks) were enrolled in a US multicenter observational study, The Prematurity and Respiratory Outcomes Program (http://clinicaltrials.gov/ct2/show/NCT01435187 ). We used multivariable logistic regression to examine the association between urine GRP in the first postnatal week and multiple respiratory outcomes: BPD, defined as supplemental oxygen use at 36 + 0 weeks postmenstrual age, and post‐PRD, defined by positive quarterly surveys for increased medical utilization over the first year (PRD score). Results: A total of 109 of 257 (42%) infants had BPD, and 120 of 217 (55%) had PRD. On adjusted analysis, GRP level more than 80 was associated with BPD (adjusted odds ratio [aOR], 1.83; 95% confidence interval [CI], 1.03‐3.25) and positive PRD score (aOR, 2.46; 95% CI, 1.35‐4.48). Urine GRP levels correlated with duration of NICU ventilatory and oxygen support and with biomarkers of oxidative stress: allantoin and 8‐hydroxydeoxyguanosine. Conclusions: Urine GRP in the first postnatal week was associated with concurrent urine biomarkers of oxidative stress and with later diagnoses of BPD and PRD.